Menguak Mitos: Diskursus Gaya Gambar Amerika, Jepang, Eropa, Gaya Gambar Indonesia dan Implikasinya - Michael Sega Gumelar (Jurnal Bahasa Rupa, 2017)
The Indonesian young generation who has the skills to draw and or who love drawing in Indonesia when this study was written more or less have believe in the myth of the existence of the American drawing style (U.S.A), Japanese drawing style, European drawing style, and eventually come into conclusion there must be an Indonesian drawing style. The watching TV culture or watching other audio-visual footage via the internet reducing significantly on reading books in printed format or in electronic media (e-Books) in Indonesia young generations. In this study reveals are there really exist drawing in American, Japanese, European, and Indonesian style.